Control interno y la gestión administrativa en la empresa Af Boullosa de la ciudad de Iquitos, periodo 2022 - Galvez Jimenez, Dennis Jesus (2023)
Internal control is an important tool in the administrative management of companies, since it is possible to adopt actions aimed at protecting the financial and non-financial resources available for the development of their operational activities, as well as timely warning of the existence of risks that could affect its results. The research is entitled "Internal Control and Administrative Management in the AF Boullosa company in the city of Iquitos, period 2022", had the objective of determining the relationship between internal control and administrative management with respect to the established period. The research was of a quantitative type and a descriptive correlational design, where the questionnaire of resolved questions was used as a data collection instrument, which was validated through expert judgment and applied to a sample of 35 workers. Finally, as a result of the analysis of the data collected, it has been possible to determine that there is a low relationship and that it is not significant between internal control and administrative management, and this is based on the Spearman's Rho correlation coefficient, which turned out to be 0.384 and its significance at 0.023.